Effect of nitrogen-containing functionalization on the electrocatalytic activity of PtRu nanoparticles supported on carbon nanotubes for direct methanol fuel cells - Cheng, Yi; Xu, C.; Shen, P.; Jiang, San Ping (elsevier, 2014)
PtRu nanoparticles (NPs) with average size of ∼3 nm are supported onto poly(diallyldimethylammonium chloride) (PDDA), polyethylenimine (PEI), 1-aminopyrene (1-AP or AP), and terahydrofuran (THF) functionalized multi-walled carbon nanotubes (CNTs) using microwave assisted self-assembly method. The PtRu/CNTs catalysts are extensively characterized by TGA, TEM, XRD, XPS, cyclic voltammetry and chronoamperometry. Non-covalent functionalization substantially improves the dispersion and distribution of PtRu NPs on CNTs. Most important, the results demonstrate that nitrogen-containing functional groups of the functionalization agents play a critical role in the electrocatalystic activity of PtRu NPs supported on CNTs. PtRu NPs supported on PEI, AP and in less extent PDDA functionalized CNTs exhibited significantly higher electrocatalystic activity and stability for the electro-oxidation of methanol as compared with PtRu supported on THF-CNTs and conventional acid-treated CNTs. The superior activity of PtRu supported on functionalized CNTs is most likely due to the strong interaction of the electron rich nitrogen-containing functional groups of the functionalization agents such as PEI, AP and in less extend PDDA and the PtRu NPs assembled on CNTs.